Synthesis and Regioselective N‐2 Functionalization of 4‐Fluoro‐5‐aryl‐1, 2, 3‐NH‐triazoles. Issue 46 (6th December 2017) - Motornov, Vladimir A.; Tabolin, Andrey A.; Novikov, Roman A.; Nelyubina, Yulia V.; Ioffe, Sema L.; Smolyar, Ivan V.; Nenajdenko, Valentine G.
Abstract : A new efficient synthetic route to 4‐fluoro‐5‐aryl‐1, 2, 3‐N H ‐triazoles was elaborated. The reactions of NaN3 with aryl‐substituted α‐fluoronitroalkenes resulted in the domino construction of the target fluorinated triazoles. Sulfamic acid is an effective promoter for this heterocyclization. The subsequent functionalization reactions of the obtained triazoles proceed highly regioselectively at the N‐2 position. The observed regioselectivity was supported by DFT calculations. Abstract : Efficient syntheses of 4‐fluoro‐5‐aryl‐1, 2, 3‐N H ‐triazoles are elaborated through the reactions of NaN3 with aryl‐substituted α‐fluoronitroalkenes. The subsequent functionalization reactions of the obtained triazoles proceed highly regioselectively at the N‐2 position. The observed regioselectivity is supported by DFT calculations.